Compound heterozygous splicing CDON variants result in isolated ocular coloboma. Issue 5 (17th August 2020) - Reis, Linda M.; Basel, Donald; McCarrier, Julie; Weinberg, David V.; Semina, Elena V.
Abstract: Ocular coloboma is caused by failure of optic fissure closure during development and recognized as part of the microphthalmia, anophthalmia, and coloboma (MAC) spectrum. While many genes are known to cause colobomatous microphthalmia, relatively few have been reported in coloboma with normal eye size. Genetic analysis including trio exome sequencing and Sanger sequencing was undertaken in a family with two siblings affected with bilateral coloboma of the iris, retina, and choroid. Pathogenic variants in MAC genes were excluded. Trio analysis identified compound heterozygous donor splice site variants in CDON, a cell‐surface receptor known to function in the Sonic Hedgehog pathway, c.928 + 1G > A and c.2650 + 1G > T, in both affected individuals. Heterozygous missense and truncating CDON variants are associated with dominant holoprosencephaly (HPE) with incomplete penetrance and Cdon−/− mice display variable HPE and coloboma. A homozygous nonsense allele of uncertain significance was recently identified in a consanguineous patient with coloboma and a second molecular diagnosis. We report the first compound heterozygous variants in CDON as a cause of isolated coloboma. CDON is the first HPE gene identified to cause recessive coloboma. Given the phenotypic overlap, further examination of HPE genes in coloboma is indicated. Abstract :